2009
DOI: 10.1243/09544119jeim679
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the resurfaced hip. Part 1: The influence of the prosthesis size and positioning on the remodelling and fracture of the femoral neck

Abstract: Abstract:Hip Resurfacing is an established treatment for osteoarthritis in young, active patients. Failure modes include femoral neck fracture and prosthesis loosening, which may be associated with medium term bone adaptation, including femoral neck narrowing and densification around the prosthesis stem.Finite Element modelling was used to indicate the effects of prosthesis sizing and positioning on bone remodelling and fracture strength under a range of normal and traumatic loads, aiming to understand these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This study also produced predictions of the full set of radiographic changes which are observed clinically around resurfacing implants, including femoral neck narrowing. In previous work (Dickinson et al 2010a), neck narrowing was predicted to be linked to a shortened horizontal femoral offset in resurfaced hips compared with healthy joints (Silva et al 2004), and the present study aimed to achieve such clinically representative prosthesis positioning and biomechanical measurements. The present study predicted a BMD reduction at the superior head -neck junction with an internal-remodelling algorithm, which would be indicative of additional external remodelling of the neck cortex, which is thin in this region.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This study also produced predictions of the full set of radiographic changes which are observed clinically around resurfacing implants, including femoral neck narrowing. In previous work (Dickinson et al 2010a), neck narrowing was predicted to be linked to a shortened horizontal femoral offset in resurfaced hips compared with healthy joints (Silva et al 2004), and the present study aimed to achieve such clinically representative prosthesis positioning and biomechanical measurements. The present study predicted a BMD reduction at the superior head -neck junction with an internal-remodelling algorithm, which would be indicative of additional external remodelling of the neck cortex, which is thin in this region.…”
Section: Discussionmentioning
confidence: 98%
“…An FE model of the geometry and materials properties of a proximal femur was generated as described in a previous article (Dickinson et al 2010a), using a CT scan from a 63-year-old male (height 1.77 m, mass 85 kg) with no known orthopaedic disease. The CT scan resolution was 0.781 mm, with 2-mm slice thickness.…”
Section: Model Generation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the cement pockets within the head in which bone cement cures, aiding torsional stability, were replaced with less stress concentrating, smooth, circular section scallops. The long stem in traditional designs is intended to act primarily as a surgical alignment aid [2], although its load bearing is thought to contribute to femoral component loosening failures, possibly through proximal stress shielding [22][23][24]. Therefore, a second perceived biomechanical advantage to the short stem was to reduce the risk of prosthesis loosening compared to traditional designs as a result of proximal femoral head and neck strain shielding, resulting from undesirable stem load-bearing [25].…”
Section: Ceramic-on-ceramic Hip Resurfacing Designmentioning
confidence: 99%